The Expected Values for the Gutman Index and Schultz Index in the Random Regular Polygonal Chains - Xinmei Liu; Qian Zhan (Molecules, 2022)
Two famous topological indices, the Gutman index and Schultz index, are studied in this article. We mainly calculate the exact analytical formulae for the expected values of the Gutman index and Schultz index of a random regular polygonal chain with n regular polygons. Moreover, we determine the average values and the extremal values of the indices in regard to the set of all these regular polygonal chains.